Milk protein consumption improves muscle performance and total antioxidant status in young soccer athletes: a randomized controlled trial (Medical Journal of Indonesia, 2020)
BACKGROUND Muscle performance and antioxidant balance are closely related to an athlete achievement. Milk proteins (whey and casein) contain essential and non-essential amino acids, which benefit muscle performance through increased antioxidant levels. This study was aimed to evaluate the effects of milk protein on muscle performance and total antioxidant status (TAS) in soccer athletes. METHODS A randomized controlled trial was conducted on 20 males 16- to 18-year-old athletes at the Central Java Soccer Club in January 2018. For 28 days, the treatment group received 24 g/d of milk protein and the control group received 24 g/d of maltodextrin. Muscle performance was measured through a 20-m sprint, shuttle run, Illinois run, standing broad jump, sit-ups, push-ups, sit-and-reach test, and one-repetition maximum (1RM) leg extension. TAS was analyzed using the 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) method. RESULTS The treatment group had a decreased shuttle run time (-0.16 [0.11] versus 0.08 [0.14] sec), greater increase in sit-ups (6.80 [2.57] versus 1.10 [2.84] times/60 sec), greater increase in push-ups (2.40 [1.78] versus 0.30 [1.77] times/60 sec), and greater increase in 1RM leg extension (32.00 [13.78] versus 3.50 [13.75] kg). After adjustments for age, energy intake, carbohydrates, and pre-interventional performance, these parameters remained significantly improved after the intervention of milk protein. The TAS increase was greater in the treatment group than in the control group (0.36 [0.32] versus -0.12 [0.20] mmol/l) before and after adjustment for age, vitamin C, iron, selenium intake, and TAS pre-treatment. CONCLUSIONS Milk protein supplementation for 28 days increased muscle performance and TAS.